Temperature Differentially Influences the Capacity of Trichoderma Species to Induce Plant Defense Responses in Tomato Against Insect Pests - Di Lelio, Ilaria; Coppola, Mariangela; Comite, Ernesto; Molisso, Donata; Lorito, Matteo; Woo, Sheridan Lois; Pennacchio, Francesco; Rao, Rosa; Digilio, Maria Cristina (Frontiers in Plant Science, 2021)
Species of the ecological opportunistic, avirulent fungus Trichoderma are widely used in agriculture for their ability to protect crops from the attack of pathogenic fungi and for plant growth promotion activity. Recently, it has been shown that they may also have complementary properties that enhance plant defence barriers against insects. However, the use of these fungi is somewhat undermined by their variable level of biocontrol activity, which is influenced by the environmental conditions. Understanding the source of this variability is essential for their profitable and wide use in plant protection. Here we focus on the impact of temperature on Trichoderma harzianum T22 and Trichoderma atroviride P1 and the defence response induced in tomato to insects. The development in vitro of these two strains was differentially influenced by temperature, and the observed pattern was consistent with temperature-dependent levels of resistance induced by them in tomato plants against the aphid Macrosiphum euphorbiae and the noctuid moth Spodoptera littoralis. Tomato plants treated with T. harzianum T22 exhibited enhanced resistance towards both insect pests at 25°C, while T. atroviride P1 proved to be more effective at 20°C. The comparison of plant transcriptomic profiles generated by the two Trichoderma species allowed the identification of specific defence genes involved in the observed response, and a selected group was used to assess by qRT-PCR the differential gene expression in Trichoderma - treated tomato plants subjected to the two temperature regimens that significantly affected fungal biological performance. These results will help pave the way towards a rational selection of the most suitable Trichoderma isolates for field applications, in order to best face the challenges imposed by local environmental conditions and by the extreme climatic shifts due to global warming.